If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + -36 = -8 Reorder the terms: -36 + -4x = -8 Solving -36 + -4x = -8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + -4x = -8 + 36 Combine like terms: -36 + 36 = 0 0 + -4x = -8 + 36 -4x = -8 + 36 Combine like terms: -8 + 36 = 28 -4x = 28 Divide each side by '-4'. x = -7 Simplifying x = -7
| (x)=5x-5 | | 4(5y-3)-3=5 | | 8w-2=-10w-30+4 | | 33b-24b-7+24=-5 | | 46x-25y=15 | | 20y-12-3y=5 | | 2t-5=18.8 | | (3x^2+11+20)+(10x^2-21x-3)= | | (6+R)+2=2(R+2) | | 497= | | -9+8r=7(-5r-1)-2 | | 6u=21-4 | | 29p-3=45 | | 1100+600+5x=700+400+8x | | 4t-13=7 | | 8x-3y=-121 | | 10x-10=3x+11 | | 5(x+5)(2x+1)=110 | | -126=7x-7(2x+11) | | 18p-3=11p-45 | | 2(x-8)+10=7x+39 | | 7+8g=55 | | 0+8n=8n | | 2(5x+2)=3x^2-10x-28 | | 0+8n=82 | | -120=4b | | -4.5-5.8= | | 12x^3+20x^2-x-6=0 | | 27+k=56 | | (x^2-5)(2x^2+3)= | | 9f+7=8f | | 120+110=180 |